The Role of Islamic Economics in Advancing Green and Sustainable Development - Meiyanda Tri Pratiwi; Ummi Nur Khalijah (Institut Agama Islam Persis Bandung, 2024)
This study discusses the role of Islamic economics in promoting green and sustainable economic development. By emphasizing the values of justice, sustainability, and environmental responsibility, Islamic economic principles are in line with the goals of a green economy that focuses on low carbon emissions, social inclusiveness, and resource efficiency. Through a qualitative research method with a literature study approach, this study examines the integration between Islamic economic values and green economic practices. The results of the study indicate that Islamic economics, through concepts such as environmental mandate (khalifah), prohibition of exploitation (riba and gharar), and the application of business ethics, can significantly support the achievement of sustainable development goals (SDGs). However, challenges in its implementation remain, such as lack of awareness, regulatory barriers, and resource limitations. This study emphasizes the importance of collaboration between policy makers, business actors, and the community in creating a more sustainable economic landscape based on ethical values. The integration of Islamic economics and green economy is expected to build a more just, inclusive, and sustainable future.